Notational analysis on the shooting play of left-handed right backcourt players in women`s handball - Nakayama, S.; Yamada, E.; Fujimoto, H.; Aida, H. (13th World Congress of Performance Analysis of Sport and 13th International Symposium on Computer Science in Sport. IACSS&ISPAS 2022, 2023)
This case study uses notational analysis to clarify the characteristics of middle/long shot play of left-handed right backs in women`s handball at the world top level. The research subjects were Anna VYAKHIREVA (RUS), Nora MØRK (NOR), and Eun-he RYU (KOR). The main results were as follows: VYAKHIREVA`s shooting play was characterized by the fact that she often uses various shooting timings and shooting step patterns which suggest that she can break out alone of one-on-one situations. In the case of MØRK, since there is no significant difference in the shooting course of up-down and left-right, it was considered that she shot while alternating with each of the opposing defenders and the goalkeeper. RYU`s shooting play was characterized by reaching the shot in a situation where two defenders made a switch. It can be inferred that two or three teammates are working together for her to create a situation where she can shoot over the defenders. The take-home message from this research is that top-level players practiced shooting play according to the situation in front of them while utilizing their form and individuality.